The Role of the Audit Tools and Linked Archive System (ATLAS) in the Enhancement of Financial Statement Audit Efficiency - Niswa, Khairun; Rahma, Alya; Ivana, Sarah Obadiah; Wardani, Neng Sri (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The development of information technology has brought significant changes to auditing practices, one of which is the use of the Audit Tools and Linked Archive System (ATLAS) as electronic audit working papers. This study aims to analyze the role of ATLAS in improving the efficiency of the financial statement audit process. The research employs a qualitative approach, with data collection techniques consisting of interviews and documentation. The findings indicate that the implementation of ATLAS assists auditors in preparing audit working papers in a more systematic, integrated, and standardized manner in accordance with the stages of the audit process. The use of ATLAS also facilitates data entry, accelerates audit execution, and reduces the risk of errors commonly associated with manual methods. Therefore, ATLAS plays an important role in enhancing the efficiency and effectiveness of financial statement audits.